A case report regarding general anesthesia management of a patient with pulmonary vein stenosis that underwent balloon dilatation and stent implantation. Issue 17 (April 2018) - Li, Fangzhou; Qiao, Guoyan; Liang, Peng; Liu, Jin
Abstract: Rationale: Pulmonary vein stenosis (PVS) is a rare cardiovascular deformity that can lead to high mortality if left untreated. Patients frequently experience multiple complications such as hemoptysis, pulmonary hypertension, bronchial venous rupture and cardiac insufficiency. Currently, pulmonary vein stenosis balloon dilatation (stent implantation) is the only treatment, and this can be performed under local or general anesthesia. However, a case report on the general anesthesia management of PVS has not been previously reported. In this case report, we discuss anesthetic considerations in patients with PVS, focusing specifically on perioperative airway and circulatory management as well as the risk evaluation, and the appropriate effective management of all potential complications intraoperatively. Patient concerns: A 58-year-old male patient was admitted because of coughing rusty sputum for during 2 years as well as experiencing dyspnea and chest distress after exertion or exercising. The difficulty breathing and chest distress had been going on for a year. This patient had undergone circumferential pulmonary vein isolation twice during the last 2 years. Diagnoses: Based on the transthoracic echocardiography and computed tomography, this patient's diagnosis was considered as pulmonary vein stenosis, pulmonary hypertension (secondary), and pulmonary arteriovenous thrombosis. Interventions: We considered that such severe patients with PVS require respiratory and circulatory supports and perhaps emergency surgical interventions. Henceforth, we administered general anesthesia to the patient and had extracorporeal membrane oxygenation (ECMO) on standby. Outcomes: The duration of the surgery was approximately 4 hours, the intraoperative vital signs were stable, no pericardial effusion was observed postoperatively, the blood flow in the pulmonary vein stent was smooth, and the patient was discharged 7 days later following rehabilitation. Lessons: This surgical procedure involving respiratory and circulatory supports requires the involvement of different medical personnel such as interventionists, anesthesiologists, and surgeons. Therefore, multidisciplinary cooperation under general anesthesia will undoubtedly benefit such patients.